Proceedings of the 2019 Conference of the North 2019
DOI: 10.18653/v1/n19-2015
|View full text |Cite
|
Sign up to set email alerts
|

Development and Deployment of a Large-Scale Dialog-based Intelligent Tutoring System

Abstract: There are significant challenges involved in the design and implementation of a dialogbased tutoring system (DBT) ranging from domain engineering to natural language classification and eventually instantiating an adaptive, personalized dialog strategy. These issues are magnified when implementing such a system at scale and across domains. In this paper, we describe and reflect on the design, methods, decisions and assessments that led to the successful deployment of our AI driven DBT currently being used by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…This format adaptation is making education more tailored to individual learners and is reducing the cost of education. Afzal et al [83] developed a dialogue-based facilitator chatbot and found that natural human language was one of the critical factors to the program's success. The natural human language can be understood as the way people normally express their thoughts.…”
Section: Dialogue-based Program Evaluationmentioning
confidence: 99%
“…This format adaptation is making education more tailored to individual learners and is reducing the cost of education. Afzal et al [83] developed a dialogue-based facilitator chatbot and found that natural human language was one of the critical factors to the program's success. The natural human language can be understood as the way people normally express their thoughts.…”
Section: Dialogue-based Program Evaluationmentioning
confidence: 99%
“…With the development of deep learning techniques, dialogue systems have been applied to a large variety of tasks to meet increasing demands. In recent work, Afzal et al (2019) built a dialogue-based tutoring system to guide learners through varying levels of content granularity to facilitate a better understanding of content. Henderson et al (2019) applied a response retrieval approach in restaurant search and booking to provide and enable the users to ask various questions about a restaurant.…”
Section: Dialogue Systemsmentioning
confidence: 99%
“…One specific type of ITS is the dialogue-based ITS, which captures the effectiveness of expert human teacher-learner interactions using natural language conversations with learners. A conversation begins when the computer agent poses a question, which initiates a series of dialogue moves directed toward relevant concepts (Afzal et al, 2019). The goal of a dialogue-based ITS is to scaffold knowledge akin to expert one-on-one human tutoring.…”
Section: Dialogue-based Itssmentioning
confidence: 99%